Mixed H/spl I.bar/2/H/spl I.bar//spl infin/ optimal PID control for superheated steam temperature system based on PSO optimization - Pu Han; Yu Huang; Zeng-Zhou Jia; Dong-Feng Wang; Yong-Ling Li (2005 International Conference on Machine Learning and Cybernetics, 2005)
A general approach is proposed to design a mixed H/spl I.bar/2/H/spl I.bar//spl infin/ optimal PID controller via particle swarm optimization (PSO). The main target of the proposed mixed control method is to find a suitable controller that minimizes the performance index of error signal subject to an unequal constraint on the norm of the closed-loop system. We can give the stabilizing domain of PID controller parameters for given plant. Inside this stabilizing domain, the optimal set of controller parameters is obtained by PSO. This new method is applied to PID controller parameters optimization of superheated steam temperature system. The simulation results demonstrate the controller has high feasibility, robustness and practical value.